Genetic Structure of Cucumber Mosaic Virus From Natural Hosts in Nigeria Reveals High Diversity and Occurrence of Putative Novel Recombinant Strains - Apalowo, Oluropo A.; Adediji, Adedapo O.; Balogun, Olusegun S.; Fakolujo, Temitope I.; Archibong, Joy M.; Izuogu, Nkechi B.; Abdelgawad, Mohamed A.; Ghoneim, Mohammed M.; Mustapha, Suleiman; Qashqari, Fadi S. I.; Batiha, Gaber E.; Atiri, Gabriel I. (Frontiers in Microbiology, 2022)
Cucumber mosaic virus (CMV, Bromoviridae: Cucumovirus), one of the most widespread plant viruses with several hosts, causes huge losses in yield quality and quantity. The occurrence of various CMV strains and high genetic diversity within the virus complicate its management. We describe the population structure of CMV in Nigeria using partial RNA1 and RNA3 gene sequences from three natural hosts: pepper (Capsicum annuum), tomato (Solanum lycopersicum), and watermelon (Citrullus lanatus). One hundred and six leaf samples were obtained from 16 locations across Nigeria, and specific primers were used to amplify the two gene fragments using PCR. Twenty-four samples tested positive for CMV using RNA1 primers, and amplicons were sequenced from 12 isolates, revealing 82.94-99.80% nucleotide and 85.42-100% amino acid sequence similarities within the population. The partial RNA3 fragment, corresponding to the complete coat protein (CP) gene, was sequenced from seven isolates, with 95.79-97.90% and 98.62-100% nucleotide and amino acid intrapopulation similarities, respectively. The isolates belonged to subgroup IB and formed distinct phylogenetic clusters in both gene sets, indicating putative novel strains. Recombination signals, supported by phylogenetic inferences, were detected within the RNA1 dataset (P ≤ 0.05) and identified a recombinant isolate within the Nigerian sequences. No recombination was detected within the CP genes. Population genetics parameters established high diversity within the Nigerian population compared to other isolates worldwide, while selection pressure estimates revealed the existence of negative selection in both gene sets. Although CMV subgroup IB strains were postulated to originate from Asia, this study reveals their prevalence across several hosts from different locations in Nigeria. To our knowledge, this is the first comprehensive description of a recombinant CMV subgroup IB isolate from West Africa, which has implications for its robust detection and overall management.